Changes in the approach to acute diverticulitis. Issue 10 (24th July 2015) - Jaung, Rebekah; Robertson, Jason; Vather, Ryash; Rowbotham, David; Bissett, Ian P.
Abstract Acute diverticulitis (AD) is one of the most common acute admission diagnoses for general surgery, and its prevalence is increasing, in part due to the ageing population. Currently, most patients who present to a tertiary hospital are admitted for a period of treatment and observation. Simple, safe and cost‐effective strategies for improving our current treatment of this condition will be invaluable in providing the most appropriate management for individual patients and for reducing the health resources expended on hospital admissions and parenteral antibiotics. AD can be categorized as uncomplicated or complicated, these two subtypes have a very different clinical course. The management of uncomplicated AD has become increasingly conservative, with a focus on symptomatic relief and supportive management. Recent research has brought into question the need for extended hospital admission and questioned the current use of antibiotics. Anti‐inflammatory agents that reduce local inflammation in uncomplicated AD may be a useful means of reducing damage caused by inflammation and aiding earlier resolution of the inflammatory response and associated symptoms. Mesalazine is an anti‐inflammatory agent that has been trialled in uncomplicated AD. Mesalazine has been shown to improve time to resolution of endoscopic and histological evidence of inflammation following an episode of AD and also reduce the rate of recurrence. In this literature review, we provide an overview of recent advances in AD classification, pathophysiology and management, and examine the possibility of introducing the use of anti‐inflammatory agents in the management of uncomplicated AD.